Seleksi Potensi Bakteri Probiotik Indigenus Riau sebagai Agen Biopreservatif Bahan Pangan - WULANDARI, NUR ASYIAH; FIBRIARTI, BERNADETA LENI; ROZA, RODESIA MUSTIKA (Jurnal Riau Biologia, 2016)
The use of synthetic preservatives is not safe for consumption and very dangerous for health.Lactic acid bacteria (LAB) is a probiotic bacterium that can produce bacteriocins asbiopreservatives agents. Bacteriocins have been widely applied as a food preservative, but itscommercial availability is still low and very expensive. This study was conducted to test the abilityof 23 isolates of local probiotic bacteria in Riau to produce bacteriocins. LAB total population wascalculated by Total Plate Count (TPC) method. LAB inhibition test against indicator bacteriaStaphylococcus aureus FNCC 0047 was conducted using well diffusion method. Bacteriocinsantimicrobial confirmatory test was performed at 100OC for 15 minutes, 30 minutes, and 60minutes. The result showed that the highest LAB population was PSG4 (22.45 x 106 cfu/ml) andthe lowest was SLK2 (4.75 x 106 cfu/ml). The greatest inhibitory activity against indicator bacteriaS. aureus FNCC 0047 was found in PSG2 (15.1 mm) and the smallest was in SLK2 (10.75 mm)with the activity of bacteriocins 2575 mm2/ml and 792.6 mm2/ml respectively. The bacteriocinsconfirmatory test showed clear zone of isolates JN5, PSG2, and SLK2 with the largest inhibitionzone was during heating for 30 minutes and 60 minutes (19.2 mm, 19.5 mm, and 16.8 mm) whilethe smallest was for 60 minutes and 15 minutes (12.8 mm, 15.6mm, and 14.7 mm).Keywords: Probiotic bacteria, biopreservatives, bacteriocins, Staphylococcus aureus FNCC 0047.